2018
DOI: 10.1080/14737140.2018.1474104
|View full text |Cite
|
Sign up to set email alerts
|

Progressive tissue biomarker profiling in non-muscle-invasive bladder cancer

Abstract: The recurrence rate of non-muscle-invasive bladder cancer (NMIBC) is up to 60% within the first year of therapy. Accurate risk stratification is necessary for patient counselling, follow-up scheduling and individualized therapeutic decision making. Current prognostic models rely on clinicopathologic features, but their discrimination remains limited when in external cohorts. Despite intense efforts regarding the value of biomarkers in prognosticating outcomes in NMIBC, clinical utility remains suboptimal. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 80 publications
0
5
1
Order By: Relevance
“…Matching findings were also reached by Baumgart et al, 2007 [22], who demonstrated notable decrease in E-cadherin marker staining in their cases from NMIBC to MIBC in 572 UBC cases. D'Andrea et al (2018) [23] examined E-cadherin as a proposed biomarker for recurrences prediction in NMIBC and although its positivity in most of the cases, E-cadherin failed to predict the recurrences in this study. Otto et al, 2017 [18], approved E-cadherin as a prognostic marker that is lost in progressive cases with above 75% positivity rate in their cases.…”
Section: Discussioncontrasting
confidence: 54%
“…Matching findings were also reached by Baumgart et al, 2007 [22], who demonstrated notable decrease in E-cadherin marker staining in their cases from NMIBC to MIBC in 572 UBC cases. D'Andrea et al (2018) [23] examined E-cadherin as a proposed biomarker for recurrences prediction in NMIBC and although its positivity in most of the cases, E-cadherin failed to predict the recurrences in this study. Otto et al, 2017 [18], approved E-cadherin as a prognostic marker that is lost in progressive cases with above 75% positivity rate in their cases.…”
Section: Discussioncontrasting
confidence: 54%
“…NMIBC treatment comprises transurethral resection of the bladder (TURB) and, depending on the risk of progression, instillation with bacillus Calmette-Guerin (BCG) or mitomycin [ 3 , 4 , 5 ]. However, high-risk NMIBC remains a challenge because 30% to 60% of patients with stage pT1 NMIBC develop local recurrence, and up to 20% experience disease progression to MIBC [ 6 , 7 , 8 ]. There is heterogeneity in stage pT1 NMIBC, and its risk stratification is based only on clinicopathological parameters that necessitate lifelong follow-up [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…P53 is considered a crucial tumor suppressor gene, encoding for a protein (p53) that plays a central role in arresting the cell cycle, activating DNA repair, and inducing apoptosis. Immunohistochemistry represents a surrogate to the analysis of p53 mutational status since nuclear immunoreactivity is highly concordant with genomic mutations (7)(8)(9). Indeed, proteins encoded by mutated p53 have prolonged half-life with an increased nuclear accumulation, which is responsible for immunohistochemical detection (10).…”
Section: P53 and Other Cell-cycle Biomarkersmentioning
confidence: 99%